CONCORDANCE OF CYTOMORPHOOLGICAL FEATURES OF CERVICAL LYMPHADENITIS SUSPECTED FOR MYCOBACTERIUM TUBERCULOSIS ON FINE NEEDLE ASPIRATION BIOPSY WITH GENEXPERT FOR MYCOBACTERIUM TUBERCULOSIS ON ASPIRATED MATERIAL - Hamza Mansur (Army Medical College Rawalpindi, 2019)
Objective: To correlate different cytomorphological presentations of cervical lymphadenitis suspected for Myco-bacterium Tuberculosis (MTB) on Fine Needle Aspiration Cytology (FNAC) with Mycobacterium Tuberculosis detection by geneXpert on aspirated material.